2012
DOI: 10.1371/journal.pone.0045435
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Corneal Epithelial Cells from Induced Pluripotent Stem Cells Derived from Human Dermal Fibroblast and Corneal Limbal Epithelium

Abstract: Induced pluripotent stem (iPS) cells can be established from somatic cells. However, there is currently no established strategy to generate corneal epithelial cells from iPS cells. In this study, we investigated whether corneal epithelial cells could be differentiated from iPS cells. We tested 2 distinct sources: human adult dermal fibroblast (HDF)-derived iPS cells (253G1) and human adult corneal limbal epithelial cells (HLEC)-derived iPS cells (L1B41). We first established iPS cells from HLEC by introducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 39 publications
2
99
0
Order By: Relevance
“…Cell replacement therapy using autologous or allogeneic adult limbal grafts has been the standard treatment for patients with severe limbal stem cell deficiency (LSCD) (Rama et al, 2010;Sangwan et al, 2011;Basu et al, 2016). However, in the case of bilateral epithelial defects and for the treatment of conditions affecting the stromal and endothelial cell layers, alternative stem cell sources such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been explored with a view to generating the various corneal cell types (Ahmad et al, 2007;Shalom-Feuerstein et al, 2012;Hayashi et al, 2012;Sareen et al, 2014;Mikhailova et al, 2014;Chan et al, 2013;Zhang et al, 2014;Chen et al, 2015;McCabe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cell replacement therapy using autologous or allogeneic adult limbal grafts has been the standard treatment for patients with severe limbal stem cell deficiency (LSCD) (Rama et al, 2010;Sangwan et al, 2011;Basu et al, 2016). However, in the case of bilateral epithelial defects and for the treatment of conditions affecting the stromal and endothelial cell layers, alternative stem cell sources such as embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been explored with a view to generating the various corneal cell types (Ahmad et al, 2007;Shalom-Feuerstein et al, 2012;Hayashi et al, 2012;Sareen et al, 2014;Mikhailova et al, 2014;Chan et al, 2013;Zhang et al, 2014;Chen et al, 2015;McCabe et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Given this, the authors suggest that adipose derived pericytes present a more preferable option for transplantation than BM-MSCs as they can be isolated 205 …”
Section: Pericytes As a Therapeutic Agentmentioning
confidence: 99%
“…Another group has reported the presence of stromal stem cells at the limbal niche and demonstrated the usefulness of these autologous, mesenchymal-like stem cells in the treatment of corneal stromal scars (Li et al 2012 ;Basu et al 2014 ). Apart from various adult stem cell sources, pluripotent stem cell (PSCs) sources such as the human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs) have been tested for their ability of to generate corneal epithelial, endothelial and stromal cells (Ahmad et al 2007 ;Yoshida et al 2011 ;Hayashi et al 2012 ;Chan et al 2013 ;Sareen et al 2014 ;Mikhailova et al 2014 ;Zhang et al 2014 ). Spontaneous differentiation of PSCs results in the generation of heterogenous cell types representing all three germ layers of the body.…”
Section: Alternate Stem Cell Sources and Treatment Modalities For Ocumentioning
confidence: 99%
“…Also, the epigenetic memory of parental somatic cells is known to infl uence lineage differentiation propensity of iPSCs. To address this problem, a couple of recent studies have attempted to generate iPSCs from limbal fi broblasts and epithelial cells and shown that these iPSCs could effi ciently differentiate into corneal cells (Hayashi et al 2012 ;Sareen et al 2014 ). These stem cell sources are amenable for large scale expansion and are suitable for genetic manipulations in vitro.…”
Section: Alternate Stem Cell Sources and Treatment Modalities For Ocumentioning
confidence: 99%